A divided schooling system: the spatial nature of secondary education in Ladybrand, Free State, South Africa. Issue 3 (3rd July 2022) - Mnguni, Phindile; Morton Mckay, Tracey Jill
ABSTRACT: School choice and commuting in Ladybrand's three high schools was explored. While all were numerically dominated by Black African children, only the fee-charging former whites-only public school, in the heart of Ladybrand, had a multiracial learner profile. Black African learners enrolled in this school hailed from mostly middle-class homes in the neighbouring Black African township of Lesotho. The homes are financially resourced. Parents are educated, married and employed in skilled or professional jobs. These learners passively commuted to school. The profile of the two no-fee schools, located in the former 'black only' designated peripheral townships, was different. Here learners are almost exclusively Black South Africans, living in poorly educated, single-parent homes. Household finances were weak with parents either unemployed or working in semi-skilled or unskilled jobs. These learners either used a subsidized government bus, mini-bus taxis or walked (in some cases long distances from neighbouring farms) to school. Parents said they selected no-fee schools on geographical proximity and low cost; whereas education quality drove choice for the former white school. The socio-economic and demographic profile of learners in no-fee versus fee-paying schools was statistically significant. Ladybrand's high schools are segregated by class, a situation reflecting much of urban South Africa.